IMPACT ASSESSMENT OF BACKGROUND RADIATION ON HABITANT AND THE MINING ENVIRONMENT AT LAPAI, AREA NIGER STATE, NIGERIA - Usman, Yusuf Tanko; Bello, S.; Yabagi, A. J.; Suleiman, I. K.; Ishaq, Y.; Salisu, U. M. (FUDMA JOURNAL OF SCIENCES, 2022)
The anticipated implication of increase in background radiation levels at mineral exploitation sites and consequence on human and environment suggested investigating the Background Ionization Radiation (BIR) levels at a mining site located at closed to the communities of Lapai LGA of Niger State, Nigeria. An in-situ method of BIR measurement at thirty points within the study area was carried out using portable GQ GMC-320 Plus radiation meter at 1.0 m elevation above ground level with GPS for geographical location. The results indicated peak BIR levels of 0.22 mR/h at some points which is abnormal compared to recommendations by International Commission on Radiation Protection (ICRP) for normal environment, while BIR at some other points it was low-ranging, with lowest at 0.0010 mR/h which is in tandem with ICRP recommendation. The absorbed doses in all the points are far below the world average value. The values for the Annual Effective Dose for the entire site agreed with the permissible limits (1.00 mSv/yr) for the general public by the ICRP for non-occupational population exposure. The study therefore revealed that the BIR levels and the doses for the mineral exploitation site does not yet constitute any negative radiological health effect at this moment on the Artesian Miners and the environs. However, there is possibility of continued increase in the BIR level due to mining activities and so continued monitoring is recommended to avert possible health hazards.